Fast policy : experimental statecraft at the thresholds of neoliberalism - Peck, Jamie; Theodore, Nikolas (University of Minnesota Press, 2015)
We inhabit a perpetually accelerating and increasingly interconnected world, with new ideas, fads, and fashions moving at social-media speed. New policy ideas, especially 'ideas that work', are now able to find not only a worldwide audience but also transnational salience in remarkably short order. 'Fast Policy' is the first systematic treatment of this phenomenon, one that compares processes of policy development across two rapidly moving fields that emerged in the Global South and have quickly been adopted worldwide conditional cash transfers (a social policy program that conditions payments on behavioral compliance) and participatory budgeting (a form of citizen-centric urban governance). Jamie Peck and Nik Theodore critically analyze the growing transnational connectivity between policymaking arenas and modes of policy development, assessing the implications of these developments for contemporary policymaking. Emphasizing that policy models do not simply travel intact from sites of invention to sites of emulation, they problematize fast policy as being real and consequential yet prone to misrepresentation. Based on fieldwork conducted across six continents and in fifteen countries, 'Fast Policy' is an essential resource in providing an extended theoretical discussion of policy mobility and in presenting a methodology for ethnographic research on global social policy.--